Unequal Scenes - Miller, John (Design/Arts/Culture, 2023)
This photographic project documents some of the world’s most extreme dividing lines of inequality using aerial photography. Seen from above, cities as diverse as Cape Town, Rio de Janeiro, Mumbai and more are portrayed as systematically exclusionary, with the urban footprints of their buildings inviting the viewer to understand each city in a unique way. The aerial nature of the photographs is reminiscent of satellite images, but presented with the color and style of a travel portfolio. By presenting such a topic as inequality through aerial photography the hope is to spark discussions on urban planning and equity.